Conditioning intensity in myelodysplastic patients aged ≥ 50 years undergoing allogeneic hematopoietic cell transplantation (allo-HCT): a study on behalf of the chronic malignancies working party of the EBMT - Henoun Loukili, Noureddine; Gras, Luuk; Koster, Linda; Blaise, Didier; Gedde-Dahl, Tobias; Maertens, Johan; Friis, Lone Smidstrup; Mielke, Stephan; Chevallier, Patrice; Passweg, Jakob R.; Byrne, Jennifer Louise; Salmenniemi, Urpu; et al. (SPRINGERNATURE, 2026)
Reduced intensity conditioning (RIC) is usually used for patients with myelodysplastic syndrome (MDS) undergoing allogeneic hematopoietic cell transplantation (allo-HCT), particularly in the elderly or those with comorbidities. The impact of conditioning intensity on patients' outcome remains controversial with clinicians' subjective opinion/ experience remaining a major guide in choosing the intensity. Here, we compare RIC versus MAC in a large EBMT retrospective study in MDS patients aged >= 50 years undergoing allo-HCT between 2014 and 2018. Among the 1393 included patients, 922 (66%) were males, and the median age at transplant was 62.8 (50.0-77.9) years. The majority of patients (n = 884; 64.3%) had MDS with excess blasts. IPSS-R recorded was very low/low (n = 598, 43%), intermediate (n = 352, 25%), and high/very high (n = 443, 32%). Karnofsky index was >= 90 in 916 (69.3%) patients, and HCT-CI >= 3 in 292(27.3%) patients. A RIC regimen was used in 1053 (75.5%) patients. Median follow-up was 27.9 months (IQR: 26.4-30.6). Both uni- and multi-variable analyses did not show any significant association between conditioning intensity and outcomes. This study highlights a lack of association between RIC/MAC regimens and outcomes in allo-HCT MDS patients. Our results support the recently published systematic review and meta-analysis, where evidence for using one conditioning regimen over another remains weak.